Mast cells contribute to alveolar bone loss in Spontaneously Hypertensive Rats with periodontal disease regulating cytokines production - Brito, Victor Gustavo Balera [UNESP]; Patrocinio, Mariana Sousa [UNESP]; Sousa, Maria Carolina Linjardi [UNESP]; Barreto, Ayná Emanuelli Alves [UNESP]; Frasnelli, Sabrina Cruz Tfaile [UNESP]; Lara, Vanessa Soares; Santos, Carlos Ferreira; Oliveira, Sandra Helena Penha [UNESP] (Public Library of Science (PLoS), 2021)
Mast cells (MCs) play a pivotal role in inflammatory responses and had been studied in inflammatory bone disorders, however, their role in alveolar bone loss induced by periodontal disease (PD) is not yet fully understood. We, therefore, aimed to evaluate the effects of MCs depletion in the PD-induced alveolar bone loss in Wistar (W) and Spontaneously Hypertensive Rats (SHRs). PD was induced by ligating the lower first molars with silk thread one day after the MCs depletion, by the pre-treatment with compound 48/80 for 4 days. After 15 days of PD induction, the hemi-mandibles were surgically collected for qRT-PCR, histological analyses, immunostaining, and ELISA. Systolic blood pressure (SBP) was verified by tail plethysmography to confirm the hypertensive status, and SHR presented SBP >150 mmHg, and previous MC depletion alone or associated with PD did not alter this parameter. SHRs showed a more severe alveolar bone loss compared to W, and MC depletion significantly inhibited this response in both strains, with a more significant response in SHRs. MCs were less abundant in 48/80+PD groups, thus validating the previous MCs depletion in our model. PD increased the number of MC in the gingival tissue of SHR. Cytokine production (TNF-α, IL-6, IL-1β, and CXCL3) was constitutively higher in SHR and increased further after PD, which was also significantly reduced in the MCs-depleted animals. PD led to an increased expression of Opn, Rankl, Rank, Vtn, Itga5, Itgb5, Trap, and Ctsk in the mandible of W and SHRs, which was reversed in MCs-depleted animals. These results suggest that MCs significantly contributes to the PD-induced alveolar bone resorption, especially in the SHR, which is associated with a more severe PD progression compared to Wistar, partly explained by these cells contribution to the inflammatory status and mediator production, stimulating osteoclast-related response markers, which were reduced after MC depletion in our experimental model.